Energy Poverty in Africa: Causes and the Way Forward, A Case of Ghana - Amarh, Benjamin Ashitey (Advances in Social Sciences Research Journal, 2025)
This paper examines the multifaceted issue of energy poverty in Africa, with a specific focus on Ghana. It defines energy poverty as the lack of access to sufficient, affordable, clean, and reliable energy for basic human and economic development. The study examines the causes of energy poverty, which include high costs of modern energy sources, low-income levels, cultural beliefs, and inefficient energy infrastructure. It also highlights the widespread reliance on traditional biomass fuels and the adverse health, environmental, and socio-economic impacts that result. The analysis reveals the deep interlinkages between energy access and development, showing how energy poverty impedes health outcomes, education, economic productivity, and gender equality. Various strategies are reviewed to tackle energy poverty, including public and private financing, investment in distributed renewable energy technologies, and comprehensive policy frameworks. Ultimately, the paper calls for integrated development planning that treats energy access as a foundational pillar of socio-economic progress in Ghana and across sub-Saharan Africa.